ANALISIS PERENCANAAN DAN PENGANGGARAN (Studi Kasus Pada Kepolisian Negara Republik Indonesia Satuan Kerja Kepolisian Resort Malang Kota) - Nurvemiyana, Rovika; Achmad, Komarudin (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aimed to analyze the Strategic Plan for Fiscal Year 2015 as the beginning of budget plan and arrangement of the Budget Plan for Fiscal Year 2015. This research used a descriptive method with a case study approach. The types of data collected in this research are primary data and which are directly from the institution through nonparticipation observationmethod. The results showed that the activity in each institution program written in budget plan (RKA) is suitable with the vision, mission, goals and objectives of the Strategic Plan. And of 11 (eleven) strategic objectives in the Strategic Plan of the Police, only 8 (eight) strategic objectives to be achieved. In addition, funds have been established in accordance with the proposal of the units of activity. Researcher recommends increased use of budget funds in any of the activities carried out in order to achieve superior public services.Keywords: Strategic Plan, Budget Plan, Work Programs And Activities